Low penetrance of autosomal dominant lateral temporal epilepsy in Italian families without LGI1 mutations. Issue 7 (26th April 2013) - Michelucci, Roberto; Pasini, Elena; Malacrida, Sandro; Striano, Pasquale; Bonaventura, Carlo Di; Pulitano, Patrizia; Bisulli, Francesca; Egeo, Gabriella; Santulli, Lia; Sofia, Vito; Gambardella, Antonio; Elia, Maurizio; et al.
Summary Purpose In relatively small series, autosomal dominant lateral temporal epilepsy (ADLTE) has been associated with leucine‐rich, glioma‐inactivated 1 (LGI1) mutations in about 50% of the families, this genetic heterogeneity being probably caused by differences in the clinical characteristics of the families. In this article we report the overall clinical and genetic spectrum of ADLTE in Italy with the aim to provide new insight into its nosology and genetic basis. Methods In a collaborative study of the Commission of Genetics of the Italian League Against Epilepsy (LICE) encompassing a 10‐year period (2000–2010), we collected 33 ADLTE families, selected on the basis of the following criteria: presence of at least two members concordant for unprovoked partial seizures with prominent auditory and or aphasic symptoms, absence of any known structural brain pathology or etiology, and normal neurologic examination. The clinical, neurophysiologic, and neuroradiologic findings of all patients were analyzed and a genealogic tree was built for each pedigree. The probands' DNA was tested for LGI1 mutations by direct sequencing and, if negative, were genotyped with single‐nucleotide polymorphism (SNP) array to search for disease‐linked copy‐number variation CNV. The disease penetrance in mutated and nonmutated families was assessed as a proportion of obligate carriers who were affected. Key Findings The 33 families included a total of 127 affected individuals (61 male, 66 female, 22 deceased). The age at onset ranged between 2 and 60 years (mean 18.7 years). Ninety‐one patients (72%) had clear‐cut focal (elementary, complex, or secondarily generalized) seizures, characterized by prominent auditory auras in 68% of the cases. Other symptoms included complex visual hallucinations, vertigo, and déjà vu. Aphasic seizures, associated or not with auditory features, were observed in 20% of the cases, whereas tonic–clonic seizures occurred in 86% of the overall series. Sudden noises could precipitate the seizures in about 20% of cases. Seizures, which usually occurred at a low frequency, were promptly controlled or markedly improved by antiepileptic treatment in the majority of patients. The interictal electroencephalography (EEG) studies showed the epileptiform temporal abnormalities in 62% of cases, with a slight predominance over the left region. Magnetic resonance imaging (MRI) or computerized tomography (CT) scans were negative. LGI1 mutations (missense in nine and a microdeletion in one) were found in only 10 families (30%). The patients belonging to the mutated and not mutated groups did not differ except for penetrance estimate, which was 61.3% and 35% in the two groups, respectively (chi‐square, p = 0.017). In addition, the disease risk of members of families with mutations in LGI1 was three times higher than that of members of LGI1‐negative families (odds ratio [OR] 2.94, confidence interval [CI] 1.2–7.21). Significance A large number of ADLTE families has been collected over a 10‐year period in Italy, showing a typical and homogeneous phenotype. LGI1 mutations have been found in only one third of families, clinically indistinguishable from nonmutated pedigrees. The estimate of penetrance and OR, however, demonstrates a significantly lower penetrance rate and relative disease risk in non–LGI1‐mutated families compared with LGI1‐mutated pedigrees, suggesting that a complex inheritance pattern may underlie a proportion of these families.